Rādhā: The Parodhā Nāyikā - Jones, Craig (My University, 1980)
This thesis is a study of the adultery theme in the major texts of Bengali Vaisnavism. Using a chronological approach to the literature a study was made of how the adultery, or parakiya, theme was used in various texts throughout this tradition. This was facilitated by focusing on the figure of Rādhā who was considered the favored consort of the cowherd god Krsna.
The literature involved is categorized into works which are considered narrative or poetic in character, and texts which are explicitly theological or apologetic. In the former group of literature is included the earliest devotional poetry of the Bengali tradition: the Gītagovinda of Jayadeva (12th century), the padavali of Vidyāpati (14th century), and the padas of Candīdās (14th century). Also included are the Dānakelikaumudī of Rūpa Gosvāmin (16th century) and the Brahmavaivarta Purāna (16th century).
What was implicit in the devotional literature mentioned above was made explicit by the Gosvāmins of Vrndāvana. The theological perspectives of Rūpa and Jīva Gosvāmin on the parakīyā issue vary from the earlier literary tradition, (see Chapt. II, sec. 2). The Tantric Sahajiya cult offered an interpretation of Rādhā's adultery in line with the Sahaja practice of taking a woman in sādhanā, (Chapt. II, sec. 3).
In the conclusion questions are raised concerning the appeal of the adultery theme in devotional literature. Offered are parallel examples of adultery in the literature of other religious traditions and an analysis of this theme in reference to love in separation. This may offer explanations as to how such a theme persisted in the literature of Bengali literature.
Keywords: Religion; Religion